Quantum Cascade Lasers in Biomedical Infrared Imaging - Bird, Benjamin; Baker, Matthew J. (Trends in biotechnology (Regular ed.), 2015)
Technological advances, namely the integration of quantum cascade lasers (QCLs) within an infrared (IR) microscope, are enabling the development of valuable label-free biomedical-imaging tools capable of targeting and detecting salient chemical species within practical clinical timeframes.